2007
DOI: 10.1080/08039480701414973
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and functional impairment in patients with personality disorders

Abstract: The study is aimed at investigating the impact of a personality disorder (PD) diagnosis, in terms of functional impairment and subjective distress, in order to better understand the burden of this diagnosis and its implications. Among the 462 consecutive psychiatric patients diagnosed with the DSM structured interview for Axis I, II and V diagnoses, almost 60% had PD. Patients with PD displayed considerable vulnerability and suffering in many domains, including finances and interpersonal relationships. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 77 publications
2
12
1
3
Order By: Relevance
“…This was contradictory to previous studies identifying impaired quality of life in individuals with PDs compared to control individuals without PDs [3][4][5][6][7]57]. Based on these studies, our hypothesis was that the presence of a PD, with subsequent functional impairment, would influence adaptation and recovery after major burn assessed as HRQoL at one year post burn.…”
Section: Discussioncontrasting
confidence: 77%
“…This was contradictory to previous studies identifying impaired quality of life in individuals with PDs compared to control individuals without PDs [3][4][5][6][7]57]. Based on these studies, our hypothesis was that the presence of a PD, with subsequent functional impairment, would influence adaptation and recovery after major burn assessed as HRQoL at one year post burn.…”
Section: Discussioncontrasting
confidence: 77%
“…Research indicates that personality-disordered individuals are more likely than individuals without personality disorder diagnoses to have global functioning impairment, including difficulties in their interpersonal life as well as in their employment history (Skodol et al, 2002). In fact, studies have shown that those with Axis II disorders are significantly more impaired in virtually all domains of social relationships and global social adjustment than those without personality disorders, those with major depressive disorder, those with anxiety disorders, and those with alcohol use disorders (Ansell, Sanislow, McGlashan, & Grilo, 2007;Norén et al, 2007;Skodol, Oldham, et al, 2005;Spitzer et al, 1995). These results seem to persist for individuals with personality disorders for a long time (Hong et al, 2005;Skodol, Johnson, Cohen, Sneed, & Crawford, 2007).…”
Section: The Impact Of Axis II On Interpersonal Functioningmentioning
confidence: 99%
“…[1][2][3] Compared with those with no PD, people with PD show higher rates of premature mortality, 4 greater engagement in health-compromising behaviours such as substance abuse, 1 greater levels of general health problems 5 and more use of health-care services. 6 PD is also associated with financial difficulties and problems maintaining jobs, 5 marital dissatisfaction and intimate partner violence, 7 crime 8 and poor quality of life. 9 These matters make a strong case for treating people with PD.…”
Section: Personality Disordermentioning
confidence: 99%